Preparation and application of Ni2Zn6O4 / NiCoP heterostructure material derived from double MOF
By constructing dual MOF-derived Ni2Zn6O4/NiCoP heterostructured materials, the problem of low capacitance performance of existing transition metal oxide electrode materials is solved, high specific capacitance and high energy density are achieved, and good cycling stability is maintained.
Patent Information
- Application Number
- CN202510329028.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-18
AI Technical Summary
The existing transition metal oxide electrode materials have low capacitance performance during cycling, and doping methods will lead to a reduced cyclic stability of the material.
By constructing a dual MOF-derived Ni2Zn6O4/NiCoP heterostructure material, a nanoheterostructure is formed by high-temperature calcination, combining the advantages of transition metal oxides and transition metal phosphides.
It achieves high specific capacitance and high energy density, with a high capacitance retention rate after 5000 cycles, and has high stability and high capacitance performance.
Smart Images

Figure CN119852104A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method of a Ni2Zn6O4 / NiCoP heterostructure material derived from dual MOF and its application as an electrode material in the field of supercapacitors. Background Art
[0002] With the development of social economy and science and technology, the demand for energy has also increased significantly, which has accelerated the consumption of non-renewable energy such as coal, crude oil, and natural gas, and aggravated environmental pollution. Although the use of green renewable energy such as wind energy, hydropower, and solar energy can reduce environmental pollution, these renewable energy sources are greatly affected by geographical factors and have the disadvantages of intermittent instability and storage difficulties. Therefore, seeking energy storage devices that can continuously and stably output has become a top priority in solving the energy crisis. For example, supercapacitors have attracted widespread attention due to their high efficiency, reasonable cost, large capacity, short discharge time, long cycle life, and environmental protection.
[0003] The electrode materials used in the field of supercapacitors include transition metal hydroxides, transition metal oxides, transition metal sulfides, transition metal phosphides, etc. Metal-organic framework material MOF is formed by metal ions or groups and organic ligands linked by coordination bonds. It has an adjustable porous structure and a high specific surface area, making it the main precursor for preparing electrode materials. At present, transition metal oxides such as NiCo2O4, CoFe2O4, and NiFe2O4 derived from MOF have been widely studied. As the positive electrode material of supercapacitors, transition metal oxides show excellent cycle stability and good cost-effectiveness. However, transition metal oxides also face some challenges in the development process. With the expansion of the application environment of supercapacitors, the requirements for the capacitance performance of electrode materials are also increasing. The shortcomings of transition metal oxides such as large impedance and low activity in the cycle process are gradually exposed. Many researchers use transition metal ion doping to form defects between materials to improve the capacitance performance of transition metal oxides, but this doping method will lead to a decrease in the cycle stability of the material. The electronegativity of the P element in transition metal phosphides (TMPs) is smaller than that of the O element and the S element, making it a type of n-type semiconductor with metal-like properties. Its strong electron delocalization effect in the sublattice makes the electron transfer ability stronger, and it has better conductivity and more redox reactions than other transition metal compounds. Therefore, the present invention proposes to combine transition metal oxides and transition metal phosphides with high capacitance performance in a way of constructing a heterostructure, so that they form a nano heterostructure at the van der Waals interface, thereby making it have the advantages of both high stability and high capacitance performance.
[0004] The interplay of structure and composition of MOF-derived materials and the synergistic mechanisms for improving the performance of supercapacitor electrode materials are still poorly understood. Summary of the invention
[0005] The purpose of the present invention is to solve the problem of low capacitor activity of transition metal oxides prepared by existing methods, and to provide a method for preparing a Ni2Zn6O4 / NiCoP heterostructure material derived from a dual MOF for preparing a new composite electrode material with high conductivity and high energy density.
[0006] A method for preparing a Ni2Zn6O4 / NiCoP heterostructure material derived from a dual MOF is completed by the following steps: 1. Preparation of ZIF-8 ① Dissolve zinc acetate and dimethyl imidazole as raw materials in methanol, and obtain mixed solution I by stirring and standing; ② Transfer the mixed solution I into a centrifuge tube for centrifugation, and wash with anhydrous ethanol to obtain the reaction product I after centrifugation; ③ Dry the reaction product I and grind it to obtain ZIF-8; 2. Preparation of ZIF-8@ZIF-67 ① Dissolve ZIF-8 and dimethylimidazole in methanol in beaker Ⅰ, dissolve cobalt nitrate in methanol in beaker Ⅱ, and perform ultrasound; ② Add the solution in beaker II into beaker I, put it into a magnetic stirrer for stirring, and let it stand to obtain a mixed solution II; ③ Transfer the mixed solution II to a centrifuge tube for centrifugation, and wash with anhydrous ethanol to obtain the reaction product II; ④ Dry the reaction product II and grind it to obtain ZIF-8@ZIF-67; 3. Preparation of NiZn-LDH@NiCo-LDH ① Dissolve ZIF-8@ZIF-67 and nickel nitrate hexahydrate in anhydrous ethanol, and obtain a mixed solution III by stirring and hydrothermal method; ② Transfer the mixed solution III to a centrifuge tube for centrifugation, and wash with anhydrous ethanol to obtain the reaction product III; ③ Dry the reaction product III and grind it to obtain NiZn-LDH@NiCo-LDH; 4. Preparation of Ni2Zn6O4 / NiCoP ① Add NiZn-LDH@NiCo-LDH and excess potassium dihydrogen phosphate separately to both ends of the porcelain boat and wrap them with foil, and put them into a tube furnace; ② Calcine at high temperature in a tube furnace, cool naturally to room temperature, and grind to obtain reaction product IV; ③ The reaction product IV was washed with deionized water and anhydrous ethanol, and then dried to obtain a dual MOF-derived Ni2Zn6O4 / NiCoP composite material.
[0007] 5. Preparation of AC / / Ni2Zn6O4 / NiCoP asymmetric supercapacitor
[0008] In a two-electrode system, 3 M KOH solution was used as the electrolyte, the battery-type material Ni2Zn6O4 / NiCoP was used as the positive electrode, and the double-layer capacitor material activated carbon (AC) was used as the negative electrode to assemble an asymmetric supercapacitor for electrochemical testing.
[0009] Compared with the prior art, the present invention has the following beneficial effects: 1. The Ni2Zn6O4 / NiCoP composite material derived from dual MOF prepared by the present invention has a high specific capacitance as an electrode material for supercapacitors, and the specific capacitance in the three-electrode system is 2683.6 F g -1 After 5000 cycles, the capacitance retention rate is 83.54%, and the specific capacitance in the two-electrode system is 268.75 F g -1 After 5000 cycles, the capacitance retention rate is 75.95%. -1 A power density of 95.56 Wh kg -1 The maximum energy density can be applied to high energy density supercapacitors; Second, the Ni2Zn6O4 / NiCoP composite material derived from dual MOF prepared by the present invention has a special heterogeneous structure. A heterogeneous structure is formed between the two materials by high-temperature calcination, which combines the advantages of high stability of transition metal oxides and high capacitance performance of transition metal phosphides. At the same time, the synergistic effect of the heterogeneous structure further increases the valence electron concentration and active area of the material, increases the contact with the electrolyte, and thus improves the conductivity and capacitance performance of the material; 3. Preparation of the present invention The Ni2Zn6O4 / NiCoP composite material derived from dual MOF prepared by the present invention has the characteristics of simple process, easy operation and low equipment requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 The external morphology of (a) ZIF-8, (b) ZIF-8@ZIF-67, (c) NiZn-LDH@NiCo-LDH, and (d) Ni2Zn6O4 / NiCoP under a scanning electron microscope (SEM) in the examples of the present invention; Figure 2 The crystal structure analysis diagram of the Ni2Zn6O4 / NiCoP composite material by X-ray powder diffractometer (XRD) in the example of the present invention; Figure 3The ZIF-8, ZIF-8@ZIF-67, NiZn-LDH@NiCo-LDH, and Ni2Zn6O4 / NiCoP prepared in the examples of the present invention were -1 Constant current charge and discharge diagram (GCD) at a current density of ; Figure 4 The Ni2Zn6O4 / NiCoP prepared in the present invention is subjected to a current density of 1-10 A g -1 Constant current charge and discharge diagram (GCD) under ; Figure 5 The Ni2Zn6O4 / NiCoP prepared in the present invention has a voltage range of 0 to 0.6 V and a resistance of 3 - 20 mV s -1 Cyclic voltammetry (CV) at a scan rate of ; Figure 6 The impedance comparison diagram (EIS) of NiZn-LDH@NiCo-LDH and Ni2Zn6O4 / NiCoP prepared in the examples of the present invention; Figure 7 The asymmetric supercapacitor AC / / Ni2Zn6O4 / NiCoP prepared in the present invention has a voltage range of 0 to 1.6 V and a capacitance of 10 - 100 mV s -1 Cyclic voltammetry (CV) at a scan rate of ; Figure 8 The asymmetric supercapacitor AC / / Ni2Zn6O4 / NiCoP prepared in the present invention has a current density of 1-10 A g -1 Constant current charge and discharge curve (GCD) at 1000 Hz; Fig. 9 The asymmetric supercapacitor AC / / Ni2Zn6O4 / NiCoP prepared in the present invention is subjected to a current density of 10 A g -1 Cyclic stability diagram below. DETAILED DESCRIPTION
[0011] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.
[0012] Specific embodiment 1: This embodiment is a method for preparing a Ni2Zn6O4 / NiCoP heterostructure material derived from a dual MOF, which is completed by the following steps: 1. Preparation of ZIF-8 ① Weigh 1.65-1.75 g zinc acetate and 2.48-2.63 g dimethylimidazole as raw materials and dissolve them in 375-400 mL methanol. Stir vigorously with a magnetic stirrer for 10-20 min, seal with plastic wrap, and let stand at room temperature for 20-22 h to obtain a mixed solution I. ② Transfer the mixed solution I to a centrifuge tube for centrifugation (speed is 6000 ~ 8000 r / min), and wash with anhydrous ethanol 3 ~ 5 times after centrifugation to obtain the reaction product I; ③ Dry the reaction product I at 50-60 °C for 16-18 h, and grind it to obtain ZIF-8; 2. Preparation of ZIF-8@ZIF-67 ① Dissolve 200 ~ 300 mg ZIF-8 and 290 ~ 430 mg dimethylimidazole in 80 mL methanol in beaker Ⅰ, and dissolve 255 ~ 380 mg cobalt nitrate hexahydrate in 50 ~ 80 mL methanol in beaker Ⅱ. Seal with plastic wrap and ultrasonicate for 20 ~ 30 min. ② Add the solution in beaker II to beaker I, put it into a magnetic stirrer and stir vigorously for half an hour, and let it stand for 10 to 12 hours to obtain a mixed solution II; ③ Transfer the mixed solution II to a centrifuge tube for centrifugation (speed is 6000 ~ 8000 r / min), and wash with anhydrous ethanol 3 ~ 5 times after centrifugation to obtain the reaction product II; ④ Dry the reaction product II at 50-60°C for 4-5 h, and grind it to obtain ZIF-8@ZIF-67; 3. Preparation of NiZn-LDH@NiCo-LDH ① Dissolve 100-200 mg ZIF-8@ZIF-67 and 300-600 mg nickel nitrate hexahydrate in 60-120 mL anhydrous ethanol, seal with plastic wrap, ultrasonicate for 10-20 min, stir at room temperature for 1-2 h, transfer the solution to a polytetrafluoroethylene reactor, react at 90-100 °C for 14-16 h, cool and stand for 5-6 h to obtain a mixed solution III; ② Transfer the mixed solution III to a centrifuge tube for centrifugation (speed is 6000 ~ 8000 r / min), and wash with anhydrous ethanol 3 ~ 5 times after centrifugation to obtain the reaction product III; ③ Dry the reaction product III at 50-60 °C for 16-18 h, and grind it to obtain NiZn-LDH@NiCo-LDH; 4. Preparation of Ni2Zn6O4 / NiCoP ① Add 100 ~ 200 mg NiZn-LDH@NiCo-LDH and excess potassium dihydrogen phosphate to both ends of the porcelain boat separately and wrap them with foil, and put them into the tube furnace; ② Through the tube furnace at 5 ℃ min -1The reaction mixture was heated to 400 °C at a rate of 100 °C, kept at that temperature for 2 h, and then naturally cooled to room temperature. The reaction product IV was obtained by grinding. ③ The reaction product IV was washed with deionized water and anhydrous ethanol, and then dried to obtain a dual MOF-derived Ni2Zn6O4 / NiCoP composite material.
[0013] 5. Preparation of AC / / Ni2Zn6O4 / NiCoP asymmetric supercapacitor
[0014] In a two-electrode system, 3 M KOH solution was used as the electrolyte, the battery-type material Ni2Zn6O4 / NiCoP was used as the positive electrode, and the double-layer capacitor material activated carbon (AC) was used as the negative electrode to assemble an asymmetric supercapacitor for electrochemical testing. Preparation of positive and negative electrodes: First, 5 mg of active material (positive electrode: Ni2Zn6O4 / NiCoP negative electrode: activated carbon), 1 mg of acetylene black, 4 mL of ethanol and 10 mL of PTFE were weighed in the electrode bottle in sequence, and placed in an ultrasonic cleaner for 40 min to fully disperse it, and then the electrode bottle containing the dispersion was placed in a 60°C oven for 4 h to dry, and then the dried paste was applied to a rectangular nickel foam (1*2cm 2 ), and finally the nickel foam is flattened with a pressure of 10 MPa.
[0015] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:
[0016] from Figure 1 It can be seen that Ni2Zn6O4 / NiCoP has obvious two-dimensional lamellar materials irregularly stacked together. This structure increases the reaction space and active area, increases the contact with the electrolyte, and thus improves the capacitance performance; Figure 2 It can be seen that the characteristic diffraction peaks of Ni2Zn6O4 / NiCoP at 36.87°, 42.83°, 62.18°, 74.53°, and 78.46° correspond to those of standard Ni2Zn6O4 (PDF#75-0273), and the characteristic diffraction peaks at 17.54°, 26.57°, 40.98°, 44.89°, and 47.57° correspond to those of standard NiCoP (PDF#71-2336), which indicates that the Ni2Zn6O4 / NiCoP composite material was successfully prepared; Figure 3 It can be seen that the Ni2Zn6O4 / NiCoP electrode has the longest discharge time and the highest specific capacitance of 2683.6 F g -1 ;from Figure 4 It can be seen that Ni2Zn6O4 / NiCoP has a clear discharge platform, the curve has good symmetry at different current densities, and has excellent rate performance; Figure 5It can be seen that the peak current of the Ni2Zn6O4 / NiCoP electrode material increases with the acceleration of the scan rate. Although the potentials of the oxidation peak and the reduction peak have a slight shift, the shape of the curve has basically not changed, which fully proves that it has a fast current response. Figure 6 It can be seen that the series resistance Rs of NiZn-LDH@NiCo-LDH and Ni2Zn6O4 / NiCoP are 0.597 and 0.575Ω, and the charge transfer resistance Rct are 1.90 and 0.955Ω, respectively. The Ni2Zn6O4 / NiCoP material has a smaller semicircle in the high-frequency region and a larger straight line slope in the low-frequency region, indicating that it has excellent conductivity. Figure 7 It can be seen that the entire CV curve shows the mixed characteristics of the two electrodes. With the increase of the scan rate, the oxidation peak and the reduction peak current increase accordingly, and the CV curve remains closed and the shape does not change. These characteristics prove that Ni2Zn6O4 / NiCoP has good reversibility as a positive electrode material; Figure 8 It can be seen that the specific capacitance of AC / / Ni2Zn6O4 / NiCoP at different current densities is 268.75, 240, 219.37, 191.25, 174.5 and 168.12 F g, respectively. -1 When the current density reaches 10 A g -1 The capacitance retention rate of AC / / Ni2Zn6O4 / NiCoP is 62.56%, which indicates that it has excellent rate performance. Fig. 9 It can be seen that at 10A g -1 After 5000 cycles at a current density of , the capacitance retention rate is 75.95%, which indicates that it has excellent cycle stability.
[0017] In summary: the Ni2Zn6O4 / NiCoP composite material prepared in Example 1 has high capacitance performance and excellent stability, and can be used as an active material for supercapacitors.
Claims
1. A preparation method and application of Ni2Zn6O4 / NiCoP heterostructure material derived from dual MOF, characterized in that This is done by: (1) Preparation of ZIF-8 ① Dissolve zinc acetate and dimethyl imidazole as raw materials in methanol, and obtain mixed solution I by stirring and standing; ② Transfer the mixed solution I into a centrifuge tube for centrifugation, and wash with anhydrous ethanol to obtain the reaction product I after centrifugation; ③ Dry the reaction product I and grind it to obtain ZIF-8; (2) Preparation of ZIF-8@ZIF-67 ① Dissolve ZIF-8 and dimethylimidazole in methanol in beaker Ⅰ, dissolve cobalt nitrate in methanol in beaker Ⅱ, and perform ultrasound; ② Add the solution in beaker II into beaker I, put it into a magnetic stirrer for stirring, and let it stand to obtain a mixed solution II; ③ Transfer the mixed solution II to a centrifuge tube for centrifugation, and wash with anhydrous ethanol to obtain the reaction product II; ④ Dry the reaction product II and grind it to obtain ZIF-8@ZIF-67; (3) Preparation of NiZn-LDH@NiCo-LDH ① Dissolve ZIF-8@ZIF-67 and nickel nitrate hexahydrate in anhydrous ethanol and perform ultrasonic treatment, and obtain a mixed solution III by stirring and hydrothermal method; ② Transfer the mixed solution III to a centrifuge tube for centrifugation, and wash with anhydrous ethanol to obtain the reaction product III; ③ Dry the reaction product III and grind it to obtain NiZn-LDH@NiCo-LDH; (4) Preparation of Ni2Zn6O4 / NiCoP ① Add NiZn-LDH@NiCo-LDH and excess potassium dihydrogen phosphate separately to both ends of the porcelain boat and wrap them with foil, and put them into a tube furnace; ② Calcine at high temperature in a tube furnace, cool naturally to room temperature, and grind to obtain reaction product IV; ③ The reaction product IV was washed with deionized water and anhydrous ethanol, and then dried to obtain a dual MOF-derived Ni2Zn6O4 / NiCoP composite material.
2. (5) Preparation of AC / / Ni2Zn6O4 / NiCoP asymmetric supercapacitor In a two-electrode system, 3 M KOH solution was used as the electrolyte, the battery-type material Ni2Zn6O4 / NiCoP was used as the positive electrode, and the double-layer capacitor material activated carbon (AC) was used as the negative electrode to assemble an asymmetric supercapacitor for electrochemical testing.
3. The preparation and application of a Ni2Zn6O4 / NiCoP heterostructure material derived from a dual MOF according to claim 1, characterized in that The molar ratio of zinc acetate, dimethylimidazole and methanol in step 1① is 1:3.35:1035; in step 1①, stirring is carried out under vigorous stirring at a speed of 600 r / min to 700 r / min for 10 to 20 min, the reaction is sealed with plastic wrap, and after stirring, the mixed solution I is allowed to stand at room temperature for 20 to 22 h to obtain the mixed solution I; in step 1②, the mixed solution I is centrifuged at a speed of 6000 to 8000 r / min for 3 min, and anhydrous ethanol is used for washing 3 to 5 times to obtain the reaction product I; in step 1③, the reaction product I is dried at 50 to 60°C for 16 to 18 h, and ZIF-8 is obtained after grinding.
4. The preparation and application of a Ni2Zn6O4 / NiCoP heterostructure material derived from a dual MOF according to claim 1, characterized in that In step 2①, the molar ratio of ZIF-8, cobalt nitrate hexahydrate, dimethylimidazole and methanol is 1:1:4:1500, beakers I and II are sealed with plastic wrap, and the ultrasonic time is 20 to 30 min; in step 2②, the solution in beaker II is quickly added to beaker I and sealed with plastic wrap, and the stirring is carried out under vigorous stirring at a speed of 600 r / min to 700 r / min. After stirring, the mixed solution II is allowed to stand at room temperature for 10 to 12 h to obtain the mixed solution II; in step 2③, the mixed solution II is centrifuged at a speed of 6000 to 8000 r / min for 3 min, and is washed with anhydrous ethanol for 3 to 5 times to obtain the reaction product II; in step 2④, the reaction product II is dried at 50 to 60 ° C for 4 to 5 h, and ZIF-8@ZIF-67 is obtained after grinding.
5. The preparation and application of a Ni2Zn6O4 / NiCoP heterostructure material derived from a dual MOF according to claim 1, characterized in that In step 3①, the molar ratio of ZIF-8@ZIF-67, nickel nitrate hexahydrate and anhydrous ethanol is 1:3:3000, sealed with plastic wrap, ultrasonic time is 10 ~ 20 min, stirring is carried out at a speed of 400 r / min ~ 500r / min for 1 ~ 2 h, after stirring, the solution is transferred to a polytetrafluoroethylene reactor for hydrothermal treatment, the hydrothermal temperature is set to 90 ~ 100 ° C, the reaction is 14 ~ 16 h, and the mixed solution III is obtained after cooling and standing for 5 ~ 6 h; in step 3②, the mixed solution III is centrifuged at a speed of 6000 ~ 8000 r / min for 3 min, and anhydrous ethanol is used for washing 3 ~ 5 times to obtain the reaction product III; in step 3③, the reaction product III is dried at 50 ~ 60 ° C for 16 ~ 18 h, and NiZn-LDH@NiCo-LDH is obtained after grinding.
6. The preparation and application of a Ni2Zn6O4 / NiCoP heterostructure material derived from a dual MOF according to claim 1, characterized in that In step 4①, the molar ratio of NiZn-LDH@NiCo-LDH to potassium dihydrogen phosphate is 1:10-20, ensuring that the phosphorus source is excessive during the reaction; in step 4②, the tube furnace is heated at 5 °C min -1 The reaction product IV is heated to 400 °C at a heating rate of 100 °C, kept at this temperature for 2 h, and then naturally cooled to room temperature, and ground to obtain the reaction product IV; in step 4③, the reaction product IV is washed with deionized water for 3 times, and then washed with anhydrous ethanol for 3 times, and dried at 50 ~ 60 °C for 10 ~ 12 h, and Ni2Zn6O4 / NiCoP is obtained after grinding.
7. The preparation and application of a Ni2Zn6O4 / NiCoP heterostructure material derived from a dual MOF according to claim 1, characterized in that The preparation of the positive and negative electrodes in step 5 is as follows: first, 5 mg of active material (positive electrode: Ni2Zn6O4 / NiCoP negative electrode: activated carbon), 1 mg of acetylene black, 4 mL of ethanol and 10 μL of PTFE are weighed in the electrode bottle in turn, and then ultrasonicated in an ultrasonic cleaner for 40 min to fully disperse them. Then, the electrode bottle containing the dispersion is placed in a 60°C oven and dried for 4 h. The dried paste is then applied to a rectangular nickel foam (1*2 cm 2 ), and finally the nickel foam is flattened with a pressure of 10 MPa.